SETTING RUANG TERBUKA DI KAWASAN WATERFRONT CITY PONTIANAK TANGGAP PANDEMI COVID-19 - Hastika Tri Aprilla; Muhammad Nurhamsyah; Bontor Jumaylinda BR Gultom (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
This research is based on the importance of open space for a city and the people in it as well as the covid-19 pandemic that happened. The covid-19 pandemic has established boundaries to prevent its spread. Things to avoid include physical contact, gathering in large numbers, and so on. Pontianak City has an open space located on the edge border of the Kapuas River, namely Waterfront City Pontianak. Waterfront City Pontianak is still crowded even though the covid-19 pandemic is happening. The number of visitors is a concern because it can become a field for the spread of the covid-19 pandemic. Based on the issues and phenomena that occurred, it was deemed necessary to have an open space setting in the Pontianak Waterfront City area that was responsive to the covid-19 pandemic. This research is related to human behavior and space, so the method that used is behavior mapping method with the type of place centered mapping. The place centered mapping method is supported by distributing questionnaires. The next thing to do is review the covid-19 health protocol, which has been determined by the Ministry of Health (Kemenkes). The results of the study show that the Waterfront City Pontianak setting has not responded to the covid-19 pandemic. Things that need to be improved or added include adding distance markers on the floor, changing the design of existing seating facilities and plant pots, providing covid-19 health post facilities, as well as providing hand washing facilities, hand sanitizers and information media for covid-19.